Ortopedik Aciller Tanı ve Tedavi Kılavuzu - Gencer, Elif Nur; Çulcu, Ahmet; Süer Doğan, İhsaniye and Yiğit, Alperen and Yeni, Teoman Bekir and Çamoğlu, Can and Ülgen, Nuri Koray and Fakıoğlu, Remzi Can and Kıran, Veli Can and Arslan, Mehmet Murat and Mert, Orhan and Sarı, Soner and Hanege, Furkan and Kaya, Özgür and Erdoğan, Eralp and Arslan, Yağmur and Gencer, Neslihan (Academician Publishing Book DOI Portal, 2023)
-